2021
DOI: 10.1038/s41598-021-97451-9
|View full text |Cite|
|
Sign up to set email alerts
|

The latitudinal dependence in the trend of snow event to precipitation event ratio

Abstract: Precipitation phase is expected to shift from solid to liquid with temperature rising, which would in turn bring challenges to regional water resource management. Although in recent decades, consistent decreasing trends in the ratio of snowfall to precipitation rate in a warming climate have been found across multiple regions, a global view of the trends in the precipitation partitioning has not been established. In this study, we investigated the global trends of annual rain and snow frequency of occurrences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Canada (Han et al, 2018); Tibetan Plateau (Wang et al, 2016); Europe (Blöschl et al, 2019;Matiu et al, 2021;Rixen & Rolando, 2013); and the whole world (Shi & Liu, 2021). Although not examined in this study, a seasonality in precipitation type shift has been reported by Wrzesien et al (2022).…”
Section: More Precipitation Falls As Rain Than As Snow (In Mid-and Hi...mentioning
confidence: 65%
See 2 more Smart Citations
“…Canada (Han et al, 2018); Tibetan Plateau (Wang et al, 2016); Europe (Blöschl et al, 2019;Matiu et al, 2021;Rixen & Rolando, 2013); and the whole world (Shi & Liu, 2021). Although not examined in this study, a seasonality in precipitation type shift has been reported by Wrzesien et al (2022).…”
Section: More Precipitation Falls As Rain Than As Snow (In Mid-and Hi...mentioning
confidence: 65%
“…Decreases in the proportion of precipitation falling as snow have been reported in almost every part of the mid-and high latitudes: the Arctic (Screen & Simmonds, 2012), western and contiguous US (Feng & Hu, 2007;Huntington et al, 2004;Knowles et al, 2006;Shi & Liu, 2021);…”
Section: More Precipitation Falls As Rain Than As Snow (In Mid-and Hi...mentioning
confidence: 99%
See 1 more Smart Citation
“…The change in snowfall to total precipitation ratio can serve as a useful indicator on how global warming impacts on hydrological cycle. In a recent study using present weather reports, Shi and Liu found that the ratio of snowfall to precipitation occurrence has been decreasing globally in the past 40 years while at high latitudes shows an increasing trend [50]. The ratio of snowfall to precipitation amount cannot be examined in their study because of the lack of snowfall data.…”
Section: Investigation Of the Snowfall To Precipitation Ratiomentioning
confidence: 98%
“…We used the National Centers for Environmental Prediction (NCEP) Automated Data Processing (ADP) operational global surface observations to obtain near-surface atmospheric variables and precipitation phase. Two data sets, ds464.0 from January 1978 to February 2007 (https://rda.ucar.edu/ datasets/ds464.0/) and ds461.0 from February 2007 to December 2019 (https://rda.ucar.edu/datasets/ds461.0/), were merged to create a longer series following Shi and Liu (2021). Variables used include near-surface temperature, dew point temperature, surface pressure, and the present weather codes ("ww" codes).…”
Section: Training and Evaluation Data Setsmentioning
confidence: 99%